Assessment of Water Quality Assurance for Communities in Mehara, Tutuala Administrative Post, Lautém Municipality - Juvencio Dos Santos; Antonino Pedro Marsal; Francisco Ruas Hornai (Journal of Social Research, 2025)
This study investigates the measures necessary to guarantee water quality for the community in the Mehara District, Tutuala Administrative Post, Lautém Municipality, Timor-Leste. Access to safe and clean water is crucial for public health, sanitation, and overall well-being, yet the region faces challenges related to water quality due to various environmental and anthropogenic factors. Key parameters such as microbial contamination, chemical pollutants, and physical characteristics of water sources were assessed. The findings revealed significant issues with water quality that could pose health risks to the local population. Factors contributing to these issues include inadequate sanitation facilities, agricultural runoff, and seasonal variations in water availability. In response, the study outlines recommendations for improving water quality, including the implementation of effective water management practices, community education on sanitation, and the establishment of regular monitoring systems for water quality assessment. By prioritizing these strategies, the aim is to enhance the safety and sustainability of water resources in Mehara District, ultimately ensuring the health and well-being of its residents.